2016
DOI: 10.1139/cjpp-2015-0596
|View full text |Cite
|
Sign up to set email alerts
|

Camel milk and bee honey regulate profibrotic cytokine gene transcripts in liver cirrhosis induced by carbon tetrachloride

Abstract: The lack of studies regarding the mechanism of the protective effects of camel milk and bee honey against hepatotoxic compounds led us to perform this study. Thirty-six male rats were divided into two main groups. The first group (n = 9) comprised control non-cirrhotic rats. The rats of the second group (n = 27) were administered carbon tetrachloride (CCl) by intraperitoneal injection to induce liver cirrhosis. The cirrhotic rats were then divided into three equal subgroups, each comprising nine animals, as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…This reduction may be due to regulation of the transcription of these pro-inflammatory cytokines by sidr honey via its antioxidant and anti-inflammatory properties. This result was in consistence with Sadek, Beltagy, Saleh, and Abouelkhair, (2016) who concluded that combinations of bee honey and camel milk downregulated the fibrotic genes in CCL4-induced liver damage.…”
Section: Discussionsupporting
confidence: 82%
“…This reduction may be due to regulation of the transcription of these pro-inflammatory cytokines by sidr honey via its antioxidant and anti-inflammatory properties. This result was in consistence with Sadek, Beltagy, Saleh, and Abouelkhair, (2016) who concluded that combinations of bee honey and camel milk downregulated the fibrotic genes in CCL4-induced liver damage.…”
Section: Discussionsupporting
confidence: 82%
“…In hepatocytes, the IR refers to increased demand for insulin to maintain glucose homoeostasis, which leads to persistent stimulation of insulin production by pancreatic B-cells and subsequently, hyperinsulinaemia (18) , as well as failure of insulin to inhibit hepatic glucose production, which is responsible for development of hyperglycaemia (47) . Sadek et al (48) revealed that CCl4 significantly increases oxidative stress, expression of the profibrotic cytokine genes such as TNF-α and TGF-β, blood glucose and insulin levels and IR index (HOMA-IR). However, these effects were abolished by camel milk either alone or in combination with bee honey because of their antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Sadek et al . ( 48 ) revealed that CCl4 significantly increases oxidative stress, expression of the profibrotic cytokine genes such as TNF-α and TGF-β , blood glucose and insulin levels and IR index (HOMA-IR). However, these effects were abolished by camel milk either alone or in combination with bee honey because of their antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used CCl 4 treated rat model of liver damage. Besides elevating the levels of liver enzymes, blood glucose, non-esterified fatty acids in the serum and glycogen in liver, CCl 4 also significantly decreases phosphorylase activity in liver and increases carbohydrate intolerance and insulin resistance ( Sadek et al, 2016 ). Administration of CCl 4 causes liver steatosis ( Cui et al, 2017 ) and therefor it has been used to develop experimental models of NAFLD ( Kanai et al, 2016 , Chheda et al, 2014 ) and NASH ( Tsuchida et al, 2018 , Owada et al, 2018 ); the latter condition is a type of NAFLD with inflammation and liver cell damage along with fat accumulation.…”
Section: Discussionmentioning
confidence: 99%